The early- and mid-term results of our endovascular aneurysm repairs in thoracic aortic pathologies - Acikgoz, Burak; Aycan Kavala, Ali; Yazicioglu, Levent; Kaya, Bulent; Ucanok, Kemalettin (Annals of Medical Research, 2021)
Aim: Endovascular therapy can be an alternative option to open surgical treatment in high-risk patients with dissecting or pure aneurysmal dilation of aorta. Endovascular therapy is associated with less complication rates, as well as shorter hospital stay and favourable blood products need perioperatively when compared to those in open surgical treatment. Our study aims to present a single center experience by evaluating the early and midterm follow-up results of thoracic endovascular aortic repairs (TEVAR). Material and Methods: Nineteen patients who underwent TEVAR procedure between March 2005 and March 2011 were evaluated retrospectively. Pre- and postoperative blood samples and computerized tomography angiograpy (CTA) results were compared. The type of stent graft used, need for blood product, postprocedural complications were evaluated.Results: The patients’ mean length of hospital stay was 12,8±6.5 days. The mean age was 56.1±8.7 years. Two patients (10.5%) were urgently taken to operation; one of these (5.2%) was exitus on the postoperative day 7. None of the patients developed thromboembolic or neurological complication. Three patients (15.7%) developed endoleaks in their early-term follow-up whereas none had endoleaks in their mid-term follow-up. There was a statistically significant difference between the preoperative and postoperative hemoglobin and hematocrit values of the patients (p0.05). Conclusion: Endovascular aneurysm repair in thoracic aortic pathologies can be an alternative to surgery in suitable cases. However, we are of the opinion that the experience of surgical team to perform this procedure with this subject will be useful in reducing the complication rates. Keywords: Thoracic; aorta; endovascular; TEVAR.
Keywords: Thoracic; aorta; endovascular; TEVAR.